Effect of Diabetes Mellitus on Clinical Outcomes and ST Segment Resolution in Patients with ST Segment Elevation Myocardial Infarction Treated with Streptokinase (Journal of the Medical College for Women & Hospital, 2026)
Background: Diabetes mellitus (DM) has a major impact on clinical outcomes for coronary artery disease (CAD), which continues to be a major source of morbidity and mortality worldwide. Diabetes mellitus (DM) worsens atherosclerosis and hinders myocardial recovery in patients with ST-segment elevation myocardial infarction (STEMI), which may have an impact on the results of streptokinase thrombolysis. Aim: The study aimed to examine the clinical outcomes and ST-segment resolution in diabetic STEMI patients receiving streptokinase treatment patients. Materials and Method: This cross-sectional study examined the clinical outcomes and ST-segment resolution of 50 diabetic and 50 non-diabetic STEMI patients receiving streptokinase treatment at Mymensingh Medical College Hospital between December 2016 and November 2017. Direct interviews, Electrocardiographs (ECGs), echocardiograms, and laboratory tests were all used in the data collection process. There were three categories for ST-segment resolution: unsuccessful (70%). The statistical analysis was conducted using SPSS version 20, with a significance threshold of p